Viabilidade econômica e desempenho de um trator agrícola utilizando biocombustível extraído do óleo de girassol - Wasilewski, Anderson (2016)
The agricultural mechanization is increasingly gaining more space in the farming sector, because it became indispensable for the agricultural development, both conventional basis and agroecological. Today it is clear that besides the oil reserves are limited and finite in a near future, they still collaborate to the pollution generated by the use of fossil fuels. Biofuels emerge as an alternative source to fossil fuels, fact that goes with the agroecological principles. The vegetable oil can be used as fuel, constituting a biofuel, produced from several oleaginous plants, being biodegradable and of renewable source. Therefore, this study aimed to evaluate the economic viability and performance of an MF 275, 4x2 agricultural tractor, fueled with commercial diesel (80%) and a mixture thereof with sunflower vegetable oil (20%). The experiment was conducted at the Universidade Estadual de Maringá Experimental Farm, in Maringá - PR. It was used the randomized block design in a factorial scheme 2 x 3 x 2 (12 treatments), with four replications. The first factor represents the commercial diesel (100%) - OV0 and a mixture of commercial diesel (80%) with sunflower vegetable oil (20%) - OV20, the second factor were the theoretical travel speeds 3, 4 and 5 km/h-1, and the third factor is the load: submitted to the tractor With Load (CC) horizontal straw chopper coupled to the tractor with actuation of the power outlet and Without Load (SC) without actuation of the power outlet. The choice of the horizontal straw chopper was made because it is a machine of preparation and management of straw and crop residues. In the exploited conditions the results showed that there was no change in fuel consumption in both tested fuels. The tractor with load got the highest skating levels related to the tractor without load. The tractor fueled with OV20 showed a time-cost 7% higher, presenting uneconomical compared to commercial diesel B S10.